A review of the Bovis Calculus’s intervention mechanism and clinical application in ischemic stroke - Xu, Ke; Deng, Bowen; Jia, Tongtong; Ren, Mihong; Chen, Hai; Zhang, Jing; Guo, Jinlin; Li, Yong; Wang, Jian (Frontiers in Pharmacology, 2025)
BackgroundBovis Calculus (BC), also named Niuhuang in Chinese, is utilized as a resuscitation drug in Traditional Chinese Medicine (TCM) for the treatment of neurological disorders. Ischemic stroke (IS) is a significant global public health issue that currently lacks safe and effective therapeutic drugs. Ongoing efforts are focused on identifying effective treatment strategies from Traditional, Complementary, and Integrative Medicine. Noticeably, BC has been used in TCM for thousands of years to prevent or treat IS-related diseases.MethodsThe historical origins of BC in the treatment of IS were investigated through the examination of ancient Chinese medical texts. Furthermore, the chemical components of BC were analyzed, and its mechanisms of action against IS were summarized using literature sourced from databases such as Web of Science, PubMed, and China National Knowledge Infrastructure. Information on Chinese medicine preparations and clinical reports was also integrated to provide an overview of modern applications and safety considerations.ResultsBC mainly includes chemical components such as bile pigments, bile acids, cholesterol, proteins amino acids, and trace elements. Additionally, the efficacy of BC in treating cerebral ischemia/reperfusion injury (CI/RI) is certain, particularly due to the components of bile pigments, bile acids, and amino acids that can interfere with the enzymatic cascade reaction of CI/RI through multiple components, targets, and pathways. The active components of BC exert neuroprotective effects by reducing microcirculation disturbance, excitatory amino acid toxicity, and oxidative stress injury in the acute stage; inhibiting inflammatory injury, apoptosis, and blood-brain barrier (BBB) disruption in the subacute stage; and promoting angiogenesis and neurogenesis in the restoration stage. Furthermore, as a crude drug, BC appears in many Chinese patent medicine (CPM) preparations for the treatment of IS, and clinical and preclinical studies have proved its safety.ConclusionThe use of BC in the treatment of IS has a long history, proven efficacy, and widespread application. Future efforts should focus on elucidating its mechanisms of action and exploring its applications.